On understandings of HIV/AIDS: conversations with migrant mineworkers at Monyakeng - Molapo, Sepetla Setsomi (My University, 2012)
This study draws on a critical realist framework to understand how a major HIV/AIDS intervention programme by a South African mining company is interpreted by migrant mine workers in the Merafong Municipality. It draws on critical realism in order to explore the tension between the limitations of social structure and the possibilities of human agency. The findings of the study are grounded in a combination of observation, personal interviews, and documents and attempts to make sense of how black mineworkers understand HIV/AIDS. When understandings of HIV/AIDS are examined in relation to the ‘good sense’ of migrant mineworkers, in this case, a variety of structures that are lodged in perception and which allow particular ways of seeing in relation to HIV/AIDS become manifest. Four ideal-typical categories are developed in order to explore understandings of HIV/AIDS, namely ‘progressives’, ‘chance-takers’, ‘indigenes’, and ‘radicals’. These positionings that the good sense of migrant mineworkers (where understandings of HIV/AIDS are concerned) make evident allow for reflection on the particular ways by which individuals at the margins of social order engage modernity in South Africa after apartheid, and how this is embodied in their everyday lives. The continuing dismissal of the world of phenomena, evident in mainstream HIV/AIDS intervention programmes, can only contribute to the negligence of embodiment, a key feature that such interventions need to take into consideration.
Ph.D. University of the Witwatersrand, Faculty of Humanties, 2012